Procedural Justice in the Criminal Enforcement of Illegal Online Lending through Electronic Evidence and Victim Protection - Nursarini Simatupang (Jurnal Hukum Replik, 2026)
This study examines procedural justice in the criminal enforcement of illegal online lending through electronic evidence and victim protection. Illegal online lending does not merely raise issues of administration and consumer protection, but may also develop into a criminal offence when accompanied by threats, extortion, fraud, misuse of personal data, or dissemination of electronic information that harms victims. This study employs a normative legal research method using statutory, conceptual, case, and limited comparative approaches. The findings show that electronic evidence plays an important role in uncovering criminal acts related to illegal online lending because most perpetrators’ conduct leaves digital traces, such as threatening messages, communication recordings, screenshots, transaction histories, application data, and bank account numbers. However, electronic evidence must be obtained, secured, verified, and submitted lawfully in order to possess evidentiary value in criminal proceedings. In addition, victim protection must be positioned as part of a fair criminal process, as victims often suffer economic losses, psychological pressure, social threats, and misuse of personal data. This study affirms that procedural justice is necessary to balance the interests of law enforcement, victim protection, and respect for the rights of suspects. Keywords: illegal online lending, procedural justice, electronic evidence, victim protection, criminal procedural law.